2012
DOI: 10.1007/s00338-012-0947-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic coral gobies reduce the feeding rate of a corallivorous butterflyfish on Acropora corals

Abstract: The obligate coral-dwelling gobiid genus Gobiodon inhabits Acropora corals and has developed various physiological, morphological and ethological adaptations towards this life habit. While the advantages of this coral-fish association are well documented for Gobiodon, possible fitness-increasing factors for the host coral are unknown. This study examines the influence of coral-dwelling gobies on the feeding behaviour of obligate corallivorous butterflyfishes. In an aquarium experiment using video observation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Nonetheless, G . sp.3 may be less exposed due to its lower movement rate between corals and its structurally more complex host coral (J. Herler, personal observations; Dirnwoeber & Herler ), reducing the investment in skin toxins (Williams et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, G . sp.3 may be less exposed due to its lower movement rate between corals and its structurally more complex host coral (J. Herler, personal observations; Dirnwoeber & Herler ), reducing the investment in skin toxins (Williams et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…). Recently, Dirnwoeber & Herler () showed that these toxins are even involved in coral predator deterrence. It is unusual for the chemical composition of an ichthyocrinotoxin to have such a wide ecological functionality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations